THD analysis of 15-level multilevel inverter using lesser number of switches with nearest level control technique - Susheela, Nunsavath; Chandra, Vilasagaram Revanth (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
The multilevel inverters are considered as the efficient power converters. Because of the predominant properties of multilevel inverters over the two-level inverters, these are acquiring more popularity. The aim of research is to minimize the number of switches as well as sources. In this paper, total harmonic distortion (THD) analysis for different modulation indices is carried out for a 15-level inverter with fewer switches. This 15-level inverter uses three asymmetrical sources with nine switching devices. Nearest level control modulation technique provides the pulses for the switching devices at fundamental switching frequency. Evaluation of THD has been carried out in MATLAB/Simulink.